Аналітичні дослідження енергетичних показників і параметрів якості струминно-щільового гомогенізатора молока - Самойчук, Кирило Олегович; Самойчук, Кирилл Олегович; Samoichuk, Kyryl; Ковальов, Олександр Олександрович; Ковалев, Александр Александрович; Kovalov, Oleksandr; Борохов, Иван Валерьевич; Борохов, Іван Валерійович; Borokhov, Ivan; Паляничка, Надія Олександрівна; Паляничка, Надежда Александровна; Palianychka, Nadiia (Мелітополь: ТДАТУ, 2019)
UK: У статті відображені результати аналітичних досліджень процесу диспергування в струминно–щільовому гомогенізаторі молока. Представлено вираз, який пов’язує середній діаметр жирових кульок після диспергування з факторами, що впливають на його величину. Зроблено аналіз раціональних значень параметрів гомогенізатора, що впливають на середній діаметр жирових кульок після диспергування. Розроблено формулу для визначення енергетичних витрат при проведенні гомогенізації та нормалізації, розглянуто вплив кожного з факторів на показники енергетичних витрат при проведенні диспергування. Проведено аналіз та визначено оптимальні значення величин, які впливають на енергетичні витрати процесу. RU: В статье отражены результаты аналитических исследований процесса диспергирования в струйно-щелевом гомогенизаторе молока. Представлено выражение, которое связывает средний диаметр жировых шариков после диспергирования с факторами, влияющими на его величину. Сделан анализ рациональных значений параметров гомогенизатора, влияющих на средний диаметр жировых шариков после диспергирования. Разработана формула для определения энергетических затрат при проведении гомогенизации и нормализации, рассмотрено влияние каждого из факторов на показатели энергетических затрат при проведении диспергирования. Проведен анализ и определены оптимальные значения величин, влияющих на энергетические затраты и качество процесса. EN: Recent studies have identified as the main factor causing a decrease in the average diameter of the fat globules the difference between the speeds of skim milk and cream. Among the structures having the possibility of implementing this principle include the lesser known device of the jet type. Developed in TSATU design milk homogenizer of the jet-plane to ensure that no foaming characteristic of counter-current-jet devices and makes it possible to avoid the obliteration of channels, represent a problem when using devices of the jet type with separate supply of cream. The article summarizes the results of analytical researches conducted to determine the parameters of the homogenizer jet-slot type, necessary to assess the available opportunities to reduce energy costs during dispersion while ensuring the average size of fat globules at the level of technologically determined values. Analytical researches have allowed us to obtain a formula that binds all the parameters that affect the average size of fat globules after homogenization. The analysis of this dependence allows us to assert that a high degree of homogenization can be achieved by providing the value of the jet-slit homogenization coefficient equal to 0.8, the diameter of the chamber at the site of the greatest narrowing of the chamber equal to 2-2.5 mm and the manufacture of the chamber having a conical profile of internal surfaces. The analytical studies of the optimal parameters of the homogenizer jet-slot type allowed to obtain a theoretical dependence, linking the energy costs of dispersion with the main parameters of the process. The analysis of the obtained dependences made it possible to establish that in order to reduce the energy costs in the homogenizer of the jet–slot type, the inner surfaces of the chamber must have a cylindrical shape, the diameter of the chamber in the place of the greatest contraction should be 3.5 mm, and the fat content of the cream supplied to the homogenizer should be less than 30-35%.
Аналитические исследования энергетических показателей и параметров качества струйно- щелевого гомогенизатора молока
An analytical study of the energy characteristics and parameters of dispersion quality in the homogenizer of milk jet-slot type
Keywords: струминно-щілинний; гомогенізатор; молоко; форма камери; енергетичні витрати; середній діаметр; жирова кулька